Die Kirche und Wehranlage von Motiș/Mortesdorf, Gemeinde Valea Viilor, Kreis Sibiu – Bau- und Nutzungsgeschichte vom Mittelalter bis in die Gegenwart / The Church and Fortifications of Motiş/Mortesdorf, Municipality of Valea Viilor, District of Sibiu – History of Construction and Use from the Middle Ages to the Present - Günther Buchinger; Doris Schön (Anastasis: Research in Medieval Culture and Art)
A team of scientists from various disciplines carried out a study of the fortified church of Mortesdorf with the aim of drawing a comprehensive picture of the history of its construction, decoration and furnishing. The interdisciplinary analysis was able to show that the nave of the medieval parish church most probably dates back to the late 13th century, while the choir was built in two construction stages in the 15th century. The mural paintings of the choir, of which only small parts are visible so far, is of particularly high artistic quality. For its art historical classification (origin of the artist, significance within Transylvanian art history) its complete uncovering would be desirable. Finally, of regional historical interest is the fact that in Mortesdorf, in contrast to many fortified churches in Transylvania, the churchyard wall was not built into a simple fortification until the 15th century and the ingredients of the first half of the 17th century (fortified towers) arose less from a fortification necessity than from a claim to represent the village, which thus wanted to show its legal equality with the areas on royal soil.